2022
DOI: 10.3390/jcm11175169
|View full text |Cite
|
Sign up to set email alerts
|

Late Presenters with ST-Elevation Myocardial Infarction: A Call to Action

Abstract: The emphasis on timely coronary reperfusion in the setting of ST-segment elevation Myocardial Infarction (STEMI) comes from older studies suggesting a significant reduction in mortality among patients treated with fibrinolytic therapy during the first hours after onset of symptoms and a progressive increase in fatal events in those presenting later [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…To achieve early reperfusion, the study emphasized the significance of cutting down on waiting times and improving care delivery systems. 20,21,22 Another study by Widimsky et al examined the association between LV function and the length of time between the onset of symptoms and reperfusion in patients undergoing primary PCI or brinolysis. The results showed that compared to delayed reperfusion, early reperfusion within 2 hours of the onset of symptoms was associated with better LV function and decreased mortality.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve early reperfusion, the study emphasized the significance of cutting down on waiting times and improving care delivery systems. 20,21,22 Another study by Widimsky et al examined the association between LV function and the length of time between the onset of symptoms and reperfusion in patients undergoing primary PCI or brinolysis. The results showed that compared to delayed reperfusion, early reperfusion within 2 hours of the onset of symptoms was associated with better LV function and decreased mortality.…”
Section: Resultsmentioning
confidence: 99%
“…During RT treatments, imaging is employed in different phases: planning, supervising and treatment response assessment, including complications [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ].…”
Section: Diagnostic Managementmentioning
confidence: 99%